Concentraciones de biofertilizante foliar enriquecido y su efecto en el rendimiento del forraje de Tithonia diversifolia "botón de oro" en Zungarococha, Perú - 2021 - Salas Ramirez, Xiomy Valeska (2022)
The research was carried out in the city of Iquitos at the National University of the Peruvian Amazon. Faculty of Agronomy, located in the community of Zungarococha, whose title is CONCENTRATIONS OF ENRICHED FOLIAR BIOFERTILIZER AND ITS EFFECT ON FORAGE YIELD OF Tithonia diversifolia "GOLDEN BUTTON" IN ZUNGAROCOCHA, PERU - 2021. The evaluation was carried out at 60 days of planting in the final field, the experimental units have 3.6 square meters and there are 24 of them, the design used is a DBCA (random complete block design), with 4 treatments and 6 repetitions and the treatments are: T0 (0% biofertilizer), T1 (20% biofertilizer), T2 (40% biofertilizer) and T3 (60% biofertilizer) and it was applied once a week. The following results were obtained. It is observed that the best yields were given in the T3 treatment (60% biofertilizer and 40% water), in plant height with 146 cm, coverage with 92%, green matter with 3.10 kg/m2 and dry matter with 0.65 kg/m2. That the best green matter yield achieved per hectare is 31,000 kilos and the lowest green matter yield was 18,200 kilos at 63 days of cutting, it occurred with the concentration of 60% and 20% of liquid biofertilizer.